2020
DOI: 10.1038/s41467-020-17191-8
|View full text |Cite|
|
Sign up to set email alerts
|

The Seminavis robusta genome provides insights into the evolutionary adaptations of benthic diatoms

Abstract: Benthic diatoms are the main primary producers in shallow freshwater and coastal environments, fulfilling important ecological functions such as nutrient cycling and sediment stabilization. However, little is known about their evolutionary adaptations to these highly structured but heterogeneous environments. Here, we report a reference genome for the marine biofilm-forming diatom Seminavis robusta, showing that gene family expansions are responsible for a quarter of all 36,254 protein-coding genes. Tandem dup… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

4
3

Authors

Journals

citations
Cited by 70 publications
(114 citation statements)
references
References 77 publications
1
106
0
1
Order By: Relevance
“…Most rhythmic protein-coding genes displayed a 24-h (92.5%) or 12-h (7.5%) periodicity, and similar to reports in other diatoms, were predominantly phasing at dusk and at night ( Figure 1C, Supplemental Data Set 2) (Smith et al, 2016;Ashworth et al, 2013;Goldman et al, 2019). We cross-referenced the 10,145 protein-coding genes that were not expressed during the diurnal cycle in a publicly available S. robusta expression atlas that reports on transcriptional activity during sexual reproduction, abiotic stress and diatom-bacterial interactions (Osuna-Cruz et al, 2020). More than half (5,315) of non-diurnal genes were transcriptionally active in at least one condition, although at lower expression levels than diurnally expressed genes (Supplemental Figure 4A).…”
Section: -2)supporting
confidence: 66%
See 3 more Smart Citations
“…Most rhythmic protein-coding genes displayed a 24-h (92.5%) or 12-h (7.5%) periodicity, and similar to reports in other diatoms, were predominantly phasing at dusk and at night ( Figure 1C, Supplemental Data Set 2) (Smith et al, 2016;Ashworth et al, 2013;Goldman et al, 2019). We cross-referenced the 10,145 protein-coding genes that were not expressed during the diurnal cycle in a publicly available S. robusta expression atlas that reports on transcriptional activity during sexual reproduction, abiotic stress and diatom-bacterial interactions (Osuna-Cruz et al, 2020). More than half (5,315) of non-diurnal genes were transcriptionally active in at least one condition, although at lower expression levels than diurnally expressed genes (Supplemental Figure 4A).…”
Section: -2)supporting
confidence: 66%
“…Evolutionary analysis of rhythmic genes points towards ancient daytime functions and diatom-specific expression at night Phylostratigraphic analysis, which explores protein homology in a wide set of species to date the origin of specific genes, revealed that rhythmic protein-coding genes were enriched in eukaryote and stramenopile age, while non-significantly rhythmic genes displayed enrichment in species-specific genes (Figure 2A). The latter group of genes was mainly enriched in genes upregulated under different stress conditions in the S. robusta expression atlas (Osuna-Cruz et al, 2020), while the set of rhythmic genes was predominantly enriched in downregulated genes under these conditions ( Figure 2B). These results suggest that while phylogenetically old rhythmic genes play a role in basal diurnal functions, young and non-rhythmic genes are more important in specific environmental contexts that are not part of the diurnal regime, a trend also observed in land plants and several microalgae (Ferrari et al, 2019).…”
Section: -2)mentioning
confidence: 99%
See 2 more Smart Citations
“…The expansion of gene families seems to be a general feature of S. robusta and is not exclusive to the LHCX genes. The large genome size of S. robusta allows for duplication events which could in turn lead to adaptive evolution (Osuna-Cruz et al, 2020). A large set of LHCX genes could be required to cope with highly variable light conditions.…”
Section: Discussionmentioning
confidence: 99%